Studying the effects of metallic components of PET-insert on PET and MRI performance due to gradient switching. (21st March 2019) - Moghadam, Narjes; Espagnet, Romain; Bouchard, Jonathan; Lecomte, Roger; Fontaine, Réjean
Abstract: Inserting positron emission tomography (PET) detection modules inside an MRI bore imposes extra challenges owing to the behavior of metallic materials in a strong magnetic field. The metallic parts even when placed outside an MRI field of view may not only disturb MRI performance, but could also increase temperature and vibrations, leading to premature failure of PET electronics. To investigate the compatibility of detection modules inside 3 T, 7 T and 9.4 T MRI bore, a theoretical study of the metal induced artifacts originating from component materials of electronic circuit is presented. The LabPET II detection module and a modified version of it in which the connector was replaced by ball grid array (BGA) were studied. In addition, the effect of eddy current and the associated heat loss on the PET detection module have been examined using COMSOL Multiphysics ® simulations for 10 kHz and 100 kHz gradient switching. Results show that displacement artifacts resulting from the presence of small amounts of ferromagnetic metal and the heating effects of metal due to gradient switching can be compensated by using the slightly modified LabPET II detection module. Thus, the LabPET II system would be MR-compatible with some minor adjustments to operate effectively inside an MRI bore without interfering with its performance.